2008
DOI: 10.1136/emj.2007.051136
|View full text |Cite
|
Sign up to set email alerts
|

Snakebite envenoming in Kerala, South India: clinical profile and factors involved in adverse outcomes

Abstract: Early administration of SAV reduces the risk of complications. The presence of leucocytosis and severe coagulopathy can predict adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
84
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 22 publications
23
84
4
1
Order By: Relevance
“…Our findings were concurrent with those of earlier studies [11][12][13][14]. In our study, predominantly, the younger population was involved (20-40 years of age), probably due to their more ambulant nature [15,[16][17][18][19]. A study which was done by Bhat et al, had also noted that 80% of the cases occurred in this age group.…”
Section: Resultssupporting
confidence: 91%
“…Our findings were concurrent with those of earlier studies [11][12][13][14]. In our study, predominantly, the younger population was involved (20-40 years of age), probably due to their more ambulant nature [15,[16][17][18][19]. A study which was done by Bhat et al, had also noted that 80% of the cases occurred in this age group.…”
Section: Resultssupporting
confidence: 91%
“…This ratio is completely in alignment of facts deducted in similar studies done elsewhere [4,[14][15][16].…”
Section: Outdoor Activitysupporting
confidence: 92%
“…This is mostly because of poor visibility and accidental stepping on the snake. Similar studies conducted in other parts of country showed relatively higher incidence of snake bitten cases between 6:00 PM and midnight [9,16,21] as found in our series.…”
Section: Diurnal Variationsupporting
confidence: 92%
See 1 more Smart Citation
“…Ariaratnam [14] proposed a syndromic approach to snake bite envenomations and our patient falls to syndrome-2 as had features of coagulopathy. Suchitra et al [15] from South India, studied the clinical characteristics, factors for complications and the outcomes of snake bite in relation to timing of polyvalent ASV administration in patients with snakebite envenomation. Among the 586 cases studied, 34% had sustained outdoor bites and snake species was identified in 34.5% of bites.…”
Section: Discussionmentioning
confidence: 99%